Carbon Nanotubes: Vibration‐Induced Deagglomeration and Shear‐Induced Alignment of Carbon Nanotubes in Air (Adv. Funct. Mater. 7/2015). (February 2015) - Miansari, Morteza; Qi, Aisha; Yeo, Leslie Y.; Friend, James R.
Abstract : A simple, dry, rapid, and chemical‐free approach is developed by J. R. Friend and team for the deagglomeration and shear‐induced alignment of commercially sourced, pristine multi‐walled carbon nanotubes in air. On page 1014 the surface acoustic waves in a piezoelectric substrate are used to generate extremely large accelerations of ≈10 Mm/s 2 that, together with the electric field on the substrate, deagglomerates the nanotubes in tens of seconds, without affecting their chemical structure. The cover image was designed by Ella Marushchenko (scientific illustrations).